2018
DOI: 10.1177/1471301218770270
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative evaluation of how a virtual dementia experience impacts medical and pharmacy students’ self-reported knowledge and attitudes towards people with dementia

Abstract: Objectives It is important for healthcare professional students to understand the experience of people with dementia, their family, and their carers. Despite person-centred educational policies, current curriculums may not adequately prepare students to meet the needs of people with dementia. This study qualitatively evaluated the impact of a virtual dementia experience on medical and pharmacy students' self-reported knowledge and attitudes towards people with dementia. Methods Ten focus groups were conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“… 17 18 20 34 36 37 39 40 Likewise to knowledge, no group difference on attitudes was found in studies with a two-group comparison. 18 37 40 Qualitative data indicated that participants did perceive an overall improvement in their knowledge and attitudes towards people living with dementia, 30 as well as knowledge and confidence in dementia care following their intervention experience. 39 …”
Section: Resultsmentioning
confidence: 99%
“… 17 18 20 34 36 37 39 40 Likewise to knowledge, no group difference on attitudes was found in studies with a two-group comparison. 18 37 40 Qualitative data indicated that participants did perceive an overall improvement in their knowledge and attitudes towards people living with dementia, 30 as well as knowledge and confidence in dementia care following their intervention experience. 39 …”
Section: Resultsmentioning
confidence: 99%
“…First, students, and especially those learning in the healthcare disciplines, will become the future professionals providing care to persons with dementia and their family members. Accordingly, a myriad of studies assessed knowledge and attitudes towards AD among nursing students (Eccleston et al, 2015;Kimzey et al, 2016;Mitchell et al, 2017;Scerri and Scerri, 2013;Shin et al, 2015), dental hygiene students (Isobe et al, 2018), and medical and pharmacy students (Gilmartin-Thomas et al, 2018). Second, as the number of persons with AD continues to rise (Prince et al, 2016), increasing numbers of young people will be interacting with these older adults as grandchildren and will most likely become family caregivers of persons with the disease (Celdran et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…VR has been used to visualize three‐dimensional (3D) representations of human anatomy and as an application for distance team‐based learning 20,132 . AR and MR simulations have been used to provide 3D models of drug‐receptor interactions and biomolecular structure, additional learning resources for medication information and pharmacogenomics, vaccination training, and immersion in patient experiences of dementia 133–139 …”
Section: Computer‐based Simulationmentioning
confidence: 99%
“…129 Studies of AR and MR simulations have shown improvement in global learning objectives and qualitative positive student feedback on learning. 133,136,138,139 However, other studies have only described student perceptions of the activities. 134,135,137 Literature describing or evaluating the use of XR simulations in educating pharmacy residents are lacking.…”
Section: Learning Outcomes Assessed Using Cbsmentioning
confidence: 99%